The effects of Ethylene gas treatment and maturity stages on postharvest quality characteristics of vapour heat treated ‘Paiola’ Papaya (Carica papaya. L) - Lee, Kok Wei (2012)
The objective to conduct this experiment was to determine the effects of exogenous ethylene gas and maturity stages on postharvest quality characteristics of vapor heat treated ‘Paiola’ papaya (Carica papaya). Papaya fruits were obtained from a farm in Lanchang, Pahang. The fruits were harvested at maturity stage 2 and treated with fungicide (0.1% Octave®) for 3 to 5 minutes. Then, the fruits were transported to the Department of Agriculture, Serdang for vapor heat treatment (VHT). The papaya fruits were treated with 46.5 ºC fruit-core temperature for 20 minutes. After VHT, the fruits were treated with 100 μL/L ethylene gas at 20 ˚C for 24 hours. Non-ethylene treated (control) fruits were also kept at 20 ˚C for 24 hours. After 24 hours, all the papaya fruits were removed from the ripening rooms and stored at ambient temperature (25 ˚C). Measurements for quality characteristics, firmness, soluble solids concentration (SSC), titratable acidity (TA), ascorbic acid content, pH, peel and pulp colour, of fruits was made when the fruits reached maturity stage 4, 5, and 6. Results showed that the exogenous ethylene applied after heat treatment had no affect on firmness, SSC, TA, ascorbic acid, pH, peel and pulp colour, after VHT. There were no interaction effects of postharvest quality characteristics between ethylene and maturity stages on VHT Paiola papaya. However, there were significant effects of maturity stages on fruit firmness, ascorbic acid content, peel and pulp colour of VHT Paiola papaya. The exogenous ethylene treatment was not necessary apply instantly on Paiola papaya after VHT since there were no signification effects on postharvest quality characteristics. The ethylene treatment may apply on VHT Paiola papaya after being exported to Japan when the endogenous ethylene production and respiration rate were recovered. Furthermore, the major problem of VHT Paiola papaya was the fruits did not achieve a desirable firmness even at MS 6. It could be prevented by reducing the period of Paiola papaya in VHT chamber.